2018
DOI: 10.4066/biomedicalresearch.29-16-2318
|View full text |Cite
|
Sign up to set email alerts
|

Multiple features and classifiers for vein based biometric recognition

Abstract: An effective fusion scheme is necessary for combining features from multiple biometric traits. This paper presents a method of fusion using multiple features from hand vein biometric traits for Multimodal biometric recognition. In the proposed method, a biometric authentication system using three different set of veins images, such as, finger vein, palm vein and dorsal vein is developed. Here the multiple features from the input vein images are extracted by applying Radon transform, Hilbert-Huang transform and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Compared to a single extraction type of feature, the fusion of many features of extraction can improve the performance of the finger vein identification system [6]. Therefore, it was found that the areas for a combination of multiple features in the feature extraction stage for the finger vein identification system need to be explored more [49].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a single extraction type of feature, the fusion of many features of extraction can improve the performance of the finger vein identification system [6]. Therefore, it was found that the areas for a combination of multiple features in the feature extraction stage for the finger vein identification system need to be explored more [49].…”
Section: Introductionmentioning
confidence: 99%
“…The recognition is done using different classifiers such as support vector machine (SVM), neural network, fuzzy, bayes classifier and k-nearest neighbour (KNN) classifiers. An accuracy above 90% was reported for all used classifies except Navie bayes classifier which provides the accuracy of around 80% which is low as compared to used classifiers [6].…”
Section: A Related Workmentioning
confidence: 82%
“…In 2018, Subramaniam and Radhakrishnan [ 89 ] developed a biometric authentication system that uses finger, palm, and dorsal vein images. After preprocessing the image, the feature extraction was performed by applying three different transformations: Hilbert–Hung, Radon, and Dual-Tree Wavelet Transform.…”
Section: Finger Vein Feature Extractionmentioning
confidence: 99%
“…J. Imaging 2021, 7, 89 2 of 30 that they remain unchanged over time and can be measured without subjecting the human to a painful process. The finger vein trait satisfies in some degree the seven factors [1] that define the suitability of a biometric trait in order to be useful for identity authentication: (1) Universality, (2) Uniqueness, (3) Permanence, (4) Measurability, (5) Performance, (6) Acceptability, and (7) Circumvention.…”
Section: Introductionmentioning
confidence: 99%